Analisis Strategi Pemasaran UMKM Kopi Arabika di Kecamatan Sinjai Barat Kabupaten Sinjai (Studi Kasus: PT. Namacca Bersinar Management): Analysis of Marketing Strategies for Arabica Coffee UMKM In Sinjai Barat District Sinjai Ragency (Case Study: PT. Namacca Bersinar Management) - Windayani, Sri; Megawati; Putra Astaman; Nurdin, Fadilah (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study aims to determine the internal factors, external factors, and marketing strategies of Arabica coffee UMKM in west Sinjai district, Sinjai Regency. The method used in this study is descriptive quantitative with observation, interview, and questionnaire techques to obtain data. The results of the study indicate that the Arabica coffee UMKM has implemented a marketing mix marketing strategy using 7Ps, namely Product, Price, Place, People, Process, Physical Evidence. And after conducting a SWOT analysis, this UMKM is in quadran I, which is a very profitable position, because at this time the UMKM PT. Namacca Bersinar Management has opportunities and strengths that can be utilized. This can be seen based on the value weight through the IFAS and EFAS matrices, where the internal factor strength has a greater value weight of 1.98 compared to the weakness value weight of 1.35. And external factors include opportunity and threats where in this external factor the opportunity position has a weight value of 1.47, this shows that the opportunity weight value is greater than the weight value of threats.